Do Housing Vacancies Induce More Crime? A Spatiotemporal Regression Analysis - Chen, Xiaojin (Crime & delinquency, 2020)
This study aims to investigate the longitudinal associations between patterns of housing vacancies, neighborhood social disorder, and crime in the city of New Orleans. Using large-scale administrative and contextual data collected from the year 2012 to 2018, our spatiotemporal regression analysis provides empirical evidence for the salient effects of housing vacancy on neighborhood level of property crime and violence. In addition, the spillover effect of housing vacancy is observed on the neighborhood level of drug offense, property crime, and violence. These results potentially identify vacant properties as a modifiable target for intervention to reduce urban crime and suggest that community-based programs aiming to enhance informal social control and collective efficacy may be as important as broken window policing programs.